Kewenangan Diskresi Kepolisian Dalam Penghentian Penyidikan - Michael Ken Lingga; Marthinus Johanes Saptenno; John Dirk Pasalbessy (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Discretionary authority is the authority possessed by the police as mandated by law to carry out their duties, especially in responding to social phenomena in society.Purposes of the Research:  This study aims to determine the form of the exercise of discretionary authority in the termination of an investigation, and what are the implications of the exercise of discretionary authority in the act of terminating an investigation.Methods of the Research: This study uses a normative legal research method, which aims to determine the form of the exercise of discretionary authority in the termination of an investigation, and what are the implications of the exercise of discretionary authority in the act of stopping an investigation.Results of the Research: The discretionary authority of the police in stopping investigations is the authority given as compensation for government duties carried out by investigators.